Understanding veterinary practitioners' responses to adverse events using a combined grounded theory and netnographic natural language processing approach. - Julie Gibson; Catherine Oxtoby; Marnie L Brennan; Kate White (PLoS ONE)
Support that mitigates the detrimental impact of adverse events on human healthcare practitioners is underpinned by an understanding of their experiences. This study used a mixed methods approach to understand veterinary practitioners' responses to adverse events. 12 focus groups and 20 interviews with veterinary practitioners were conducted and analysed using grounded theory principles. Experiencing stress, externalising facts and feelings, morally contextualising events and catalysing personal and professional improvements were identified as components of practitioners' response. Natural language processing content analysis of posts regarding involvement in adverse events (n = 572) written by members of a veterinary member-only Facebook group was also performed, to categorise and count words within texts based on underlying meaning. Percentile scores of four summary variables along with relative frequency of function, psychological process and time orientation words used were recorded and compared with content analysis of posts where members discussed euthanasia (n = 471) and animal health certification (n = 419). Lower authenticity scores (reflecting lower honesty), differences in clout scores (reflecting dominance) and higher frequencies of moralisation, future focus, prosocial behaviour and interpersonal conflict were observed in the adverse event group compared to either comparison group. Analytical thinking scores (reflecting logical thinking) and frequencies of total, positive and negative emotion, anxiety, anger and cognitive processing words (reflecting debate) were not significantly different between the adverse events and euthanasia groups. Integration of findings confirmed and expanded inferences made in both studies regarding the emotionally detrimental impact of adverse events and the role that peer-to-peer mediated reflection and learning plays in mitigating pathologisation of responses in the aftermath of adverse events. Discordance in findings related to practitioners' intentions and expressions of honesty suggest that work is needed to normalise open discussion about adverse events. Findings may be used to lever, and to inform, peer-to-peer support for practitioners in relation to veterinary adverse events.